Revitalization of Gamelan Music to Support the Sustainability of Bantengan Arts at Padepokan Galogo Djati - Ana Sopanah; Istiadi Istiadi; Devita Sari; Irfany Rupiwardani (TGO Journal of Community Development, 2026)
This service program aims to strengthen the sustainability of Bantengan art through the revitalization of gamelan music at Padepokan Galogo Djati, Malang Regency. The main focus is directed at increasing the availability of traditional musical instruments, strengthening members' capacity in playing gamelan, and integrating gamelan in Bantengan exercises and performances. The activity was carried out with a participatory-based community empowerment approach. The stages include identification of partner conditions, coordination and socialization of the program, provision of a set of gamelan, gamelan game training, training assistance, implementation in Bantengan performances, and sustainability evaluation. This model places the community as an active subject in the process of cultural preservation. The main intervention in the form of providing gamelan has succeeded in overcoming the limitations of traditional musical facilities. Padepokan members received basic technical training, coordination between players, and music synchronization with the Bantengan movement. The results of the activity showed an increase in musical capacity, the use of gamelan in training, and the re-strengthening of the traditional musical character of Bantengan which previously used instant music or DJ. Gamelan functions as a cultural infrastructure that supports the connection between means, skills, performance practices, and the regeneration of art actors. This service program proves that the provision of gamelan accompanied by training and mentoring is more effective than just providing physical facilities. Gamelan is a cultural asset that strengthens the Bantengan art ecosystem through sustainable practices, knowledge inheritance, and community interaction. In the future, sustainability is directed at intensifying the use of gamelan, digital documentation, educational content development, and collaboration with village governments, universities, and creative economy actors.